Mechanism of the Effect of Protein DJ-1 on Changes in the Meat Quality of Qinchuan Cattle during Postmortem Aging - ZHANG Jing, ZHAO Wenxiu, SI Jianfang, CAO Songmin, LI Yalei, LUO Ruiming (Shipin Kexue)
In order to explore the effect of protein/nucleic acid deglycase DJ-1 (DJ-1) expression on the meat quality of Qinchuan cattle during postmortem aging, the longissimus dorsi muscle of Qinchuan cattle slaughtered at 25 months of age was aged at 4 ℃ postmortem and evaluated for meat quality, DJ-1 expression and relative levels of reaction oxygen species (ROS) after 0, 2, 4, 6 and 8 days. The correlation between DJ-1 expression and meat quality indexes and ROS was analyzed. Four-dimensional label-free quantitative (4D-LFQ) proteomics was deployed to analyze DJ-1 and the related differential proteins. The results showed that with the increase in aging time, the pH decreased first and then increased, the L*, a*, shear force, centrifugal loss and drip loss increased first and then decreased, and the b*, ROS and DJ-1 expression continued to increase. DJ-1 expression was significantly positively correlated with centrifugal loss, L*, b* and ROS (P 0.05), leading us to conclude that changes in DJ-1 expression during postmortem aging is closely related to beef tenderness. 4D-LFQ proteomics revealed that DJ-1 and its functionally related differential proteins promoted structural changes of beef muscle during postmortem aging by forming a homodimer, binding to kinases, ion channels and ubiquitin proteases, and regulating the apoptosis signaling pathway through proteasomal protein decomposition, glycolysis and the regulation of oxidative stress response. At the same time, they caused changes in the intracellular environment through complex biochemical reactions, which in turn affected beef quality attributes of Qinchuan cattle such as tenderness.